Configuring electronic states in an atomically precise array of quantum boxes - Nowakowska, Sylwia; Wäckerlin, Aneliia; Piquero‐Zulaica, Ignacio; Nowakowski, Jan; Kawai, Shigeki; Wäckerlin, Christian; Matena, Manfred; Nijs, Thomas; Fatayer, Shadi; Popova, Olha; Ahsan, Aisha; Mousavi, S. Fatemeh; et al. (Small, 2016)
A 2D array of electronically coupled quantum boxes is fabricated by means of on-surface self-assembly assuring ultimate precision of each box. The quantum states embedded in the boxes are configured by adsorbates, whose occupancy is controlled with atomic precision. The electronic interbox coupling can be maintained or significantly reduced by proper arrangement of empty and filled boxes.